Hepatopancreas-Intestinal Health in Grass Carp (Ctenopharyngodon idella) Fed with Hydrolyzable Tannin or Rapeseed Meal - Jingting Yao; Ying Hang; Xueming Hua; Ningyu Li; Xiang Li (Aquaculture Nutrition)
This study evaluated the effect of dietary rapeseed meal (RM) and hydrolyzable tannin on grass carp (Ctenopharyngodon idella) and determined the possible role of tannin on health when RM was added to the diet. Eight diets were formulated. Four were semipurified-diets with 0, 0.75, 1.25, and 1.75% hydrolyzable tannin (T0, T1, T2, and T3), and the other four were practical diets containing 0, 30, 50, and 70% RM (R0, R30, R50, and R70), which had similar tannin contents as semipurified-diets. After the 56 d feeding trial, the antioxidative enzymes and relative biochemical indexes showed a similar tendency in practical and semipurified groups. In hepatopancreas, superoxide dismutase (SOD) and catalase (CAT) activities increased with RM and tannin levels, respectively, while glutathione (GSH) content and glutathione peroxidase (GPx) activity increased. Malondialdehyde (MDA) content increased and decreased in T3 and R70, respectively. In the intestine, MDA content and SOD activity increased with RM and tannin levels, while GSH content and GPx activity decreased. The expression levels of interleukin 8 (IL-8) and interleukin 10 (IL-10) were upregulated with RM and tannin levels, and the Kelch-like ECH-associated protein 1 (Keap1) expression was upregulated in T3, whereas it was downregulated in R50. This study demonstrated that 50% of RM and 0.75% of tannin induced oxidative stress, injured hepatic antioxidant ability, and resulted in intestinal inflammation in grass carp. Therefore, the tannin in rapeseed meal cannot be neglected in aquatic feeding.